2010
DOI: 10.5251/abjna.2010.1.3.232.237
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethrel in aqueous solution and ethylene released from ethrel on guava fruit ripening

Abstract: The effect of ethrel in aqueous solutions at 250, 500 and 1000 ppm and ethylene released from ethrel at 250, 500 and 1000 ppm was evaluated on fruit ripening of white-and pink-fleshed guava fruits. Ripening was enhanced in all treated fruits of both guava types at all concentrations used. The ripening rate progressively increased with increase in concentration. Ethylene released from ethrel was more effective in triggering fruit ripening than dipping fruits in aqueous solution of ethrel. Depending on concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 6 publications
6
11
0
Order By: Relevance
“…The decrease in firmness, during ripening may be due to breakdown of insoluble protopectin into soluble pectin or by cellular disintegration leading to membrane permeability (Brinston et al, 1988). It was reported that post-harvest treatment with ethrel promoted ripening of mango fruits, and the treated fruits were less firm than the treated ones (Mohamed Nour and Abu Goukh, 2010). A similar drop in flesh firmness was reported in guava Abu Goukh and Bashir, 2003) and mango (Venkatesan and Tamilmani, 2010).…”
Section: Effect On Decaysupporting
confidence: 51%
See 2 more Smart Citations
“…The decrease in firmness, during ripening may be due to breakdown of insoluble protopectin into soluble pectin or by cellular disintegration leading to membrane permeability (Brinston et al, 1988). It was reported that post-harvest treatment with ethrel promoted ripening of mango fruits, and the treated fruits were less firm than the treated ones (Mohamed Nour and Abu Goukh, 2010). A similar drop in flesh firmness was reported in guava Abu Goukh and Bashir, 2003) and mango (Venkatesan and Tamilmani, 2010).…”
Section: Effect On Decaysupporting
confidence: 51%
“…Kulkarni et al (2004) reported an increase in TSS and sugars in mango fruits treated with ethrel. Post-harvest treatments with ethylene or ethrel were reported to induce fruit ripening and increased TSS in oranges (El Rayes, 2000) and mangoes (Siddiqui and Dhua, 2009;Mohamed Nour and Abu-Goukh, 2010;Venkatesan and Tamilmani, 2013). The increase in TSS during ripening might be due to the alteration or transformation in cell wall structure and break down of complex carbohydrates, pectic substances, hemicellulose or other polysaccharide into simple sugars and dehydration of fruits during storage (Kittur et al, 2001).…”
Section: Effect On Total Soluble Solids (Tss)mentioning
confidence: 99%
See 1 more Smart Citation
“…Parameters Studied: Respiration rate was determined by the total absorption method and was expressed in mg CO 2 per kilogram per hour (Mohamed-Nour and Abu-Goukh, 2010). Total soluble solids (TSS) were determined for the fruit juice extracted by pressing the fruit pulp in a garlic press using a Kruss hand refractometer (model HRN-32).…”
Section: Methodsmentioning
confidence: 99%
“…Fruit length and width were measured by varnier caliber (Whiter-Grew Model) and were expressed in centimeters. Respiration rate was determined in a flowing system by total absorption method and expressed in mg CO 2 per kg-hr (Mohamed-Nour and Abu-Goukh, 2010). Fruit flesh firmness was determined by Magness and Taylor firmness tester (D.Ballauf Meg Co.) equipped with an 8 mm-diameter plunger tip.…”
Section: Methodsmentioning
confidence: 99%